Density functional theory study of the α → ω martensitic transformation in titanium induced by hydrostatic pressure - Jafari, M.; Nobakhti, M.; Jamnezhad, H.; Bayati, K. (Condensed Matter Physics, 2013)
The martensitic α → ω transition was investigated in Ti under hydrostatic pressure. The calculations were carried out using the density functional theory (DFT) framework in combination with the Birch-Murnaghan equation of state. The calculated ground-state properties of α and ω phases of Ti, their bulk moduli and pressure derivatives are in agreement with previous experimental data. The lattice constants of α and ω-phase at 0 K were modeled as a function of pressure from 0 to 74 GPa and 0 to 119 GPa, respectively. It is shown that the lattice constants vary in a nonlinear manner upon compression. The calculated lattice parameters were used to describe the α → ω transition and show that the phase transition can be obtained at 0 GPa and 0 K.